Microstructrual evolution of all-wet-processed CIGS films using Raman spectroscopy - Choi, Hee Soo; Choi, Eunmi; Kim, Areum; Yoon, Sung Pil; Pyo, Sung Gyu (WILEY-V C H VERLAG GMBH, 2014)
We report a wet process deposition in order to identify a cost-effective processing scheme for CuIn1-xGaxSe2 (CIGS) layers on molybdenum/soda lime glass substrates from a Cu-In-Ga precursor solution. We employed a spin coater at various settings to evaluate the uniformity of the resulting CIGS solar cell layer. After the CIGS precursor film was deposited, we applied a selenization process. In the selenization process, we used a controlled temperature RTA system and compared it to a noncontrolled temperature system. We investigated the morphological properties for different selenization temperature treatments. We used Raman mapping to detect binary compounds and found the binary compound effect on the film. Raman mapping results show that the density of the binary compound in the CIGS layer increased with selenization temperature, and at 600 degrees C, the density of the binary compounds was highest. (C) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: CU(IN,GA)SE-2 SOLAR-CELLS; THIN-FILMS; BACK CONTACTS; SE VAPOR; EFFICIENCY; SELENIZATION; FABRICATION; SINGLE; CU; PRECURSORS